Implementation of Outdor Learning Method on Asmaul Husna Learning - Abid, Moh. Khusnul; Hidayah, Maulida Nurul; Umayya, Meigi Safira; Zahro, Fatimatuz; Musdalifah, Musdalifah; Achmad, Syaefudin (Yayasan Indonesia Emerging Literacy Education, 2025)
This study aims to determine the effectiveness of outdoor learning methods in learning asmaulhusna material in seventh grade moral creed subjects. This research uses field research method with descriptive qualitative approach. Data collection techniques through interviews and observations. Data validity test using triangulation. The informants of this research are the principal of MTs Raudlatul Furqan, moral creed subject teachers, and students. The results showed an increase in student learning outcomes in understanding the given asmaulhusna material. The outdoor learning method is used to provide variations in the delivery of learning materials and invite students to recognize and interact with the surrounding environment. By focusing on the study of outdoor learning methods on asmaulhusna material, the results of this study can be a reference for Islamic education institutions in delivering asmaulhusna learning material to students through outdoor learning methods.